Acid Mine Drainage: Effect of acid mine drainage on water and soil resources within the Bogoso/Prestea Mine Resource. (Bogoso Concessional Area) - Afriyie – Debrah, Charles (2011)
A thesis submitted to the Department of Applied & Theoritical Biology, Faculty of Bioscience, College of Science, Kwame Nkrumah University of Science & Technology, Kumasi in partial fulfilment of the requirements for the degree of Master of Science. (Environmental science)